Nonprofit Version 2.0: Are Nonprofits Allowed to Reinvent Themselves? - Cannon, Sheila (My University, 2020)
This is not a tale about how two nonprofits achieved success, neither is this a cautionary tale about how they didn’t. We shall neither provide council on how a nonprofit might achieve its mission nor on how it might create a good mission for itself. Instead we shall sojourn to the barely touched lands of what it might mean to have an existential crisis as a nonprofit: mission-success. Once upon a time, born on the eve of World War II, the National Foundation for Infantile Paralysis (NFIP) was a systematic program created to uncover the mysteries of polio and to lend a helping hand to Americans suffering from the disease. It achieved instantaneous popularity, reflecting that of its founder Franklin D. Roosevelt. Little was known about Polio then. However, soon fortune struck. The Polio vaccine was invented, and a fearsome disease was put to rest. Mission accomplished! But what of the NFIP? Where would it go from here and did this mean closure? And how could the NFIP respond to successfully completing the very purpose it had been created for? It attempted to fight Arthritis, but those efforts were wasted. Very little has been said about what happens to nonprofits post-mission success, perhaps because mission success represents the single greatest achievement for any organisation. Is closure an inevitable next step? A study conducted in 2007 indicates that mission completion was the primary cause for closure among Spanish Nonprofit Associations. Closing shop, though easier, may not be the only option it would seem. Professor Sheila M Cannon and her team believe that social organisations can effectively and efficiently shift their focus to address new related challenges once they have successfully achieved what they set out to do, rather than recreating new organisations each time. However, most existing advice to nonprofits is to avoid “mission drift” at all costs.
PUBLISHED
Keywords: Nonprofit organisations; Nonprofit organisations